Pembangunan Ekonomi Berkelanjutan Indonesia: Interaksi Dinamis Ekonomi Digital, Emisi Karbon, Pengangguran dan Pertumbuhan Ekonomi Hijau - Tanjung, Ahmad Albar; Muliyani, Muliyani; Anjeli, Rani (Jurnal Samudra Ekonomi dan Bisnis, 2026)
Green economic growth is one of the goals of sustainable economic development. This study was conducted to investigate the dynamic interaction between the digital economy, unemployment, carbon emissions and green economic growth in Indonesia. The research data uses secondary data from 1990 to 2021 on an annual basis, resulting in a total of 32 observations. The data sources are from the Central Statistics Agency and the World Bank, with an estimation approach using the ARDL method. The results show that the digital economy has a positive and significant effect on green economic growth, unemployment has a negative and significant effect on green economic growth, while carbon emissions have an insignificant negative effect on green economic growth in Indonesia. The implication of this research is that the government needs to accelerate the digital transformation of the productive sector. The alignment of digitization targets, labor absorption, and emission control in the sustainable development goals (SDGs) and national policies is also necessary.